THE CONCEPT OF JUSTICE (‘ADL) IN ISLAMIC ECONOMICS AND ITS CONTEMPORARY APPLICATION: A NORMATIF LITERATURE REVIEW - Alvinandra Prasetya (PT. Samudra Solusi Profesional, 2025)
Justice (‘adl) constitutes a foundational principle in Islamic economic thought, shaping not only ethical considerations but also institutional arrangements and socio-economic policies. Unlike conventional economic systems that often prioritize efficiency and growth, Islamic economics embeds justice as a normative objective aimed at ensuring equitable distribution, preventing exploitation, and promoting social welfare (maslahah). This study conducts a systematic normative literature review to examine the conceptual foundations of justice (‘adl) in Islamic economics and to explore its relevance in addressing contemporary economic challenges, particularly income inequality and social disparity. Drawing on classical Islamic sources, modern Islamic economic scholarship, and contemporary socio-economic data, this article synthesizes key perspectives on distributive, transactional, and social justice within the Islamic economic framework. The review highlights that justice in Islamic economics extends beyond formal equality, emphasizing the fulfillment of rights and obligations according to Shariah principles. Instruments such as zakat, waqf, profit-sharing contracts, and the prohibition of riba represent institutional mechanisms designed to operationalize justice in economic life. However, empirical realities in many Muslim-majority countries indicate persistent inequality. In Indonesia, for instance, the Gini ratio remained at 0.375 in March 2025, reflecting ongoing disparities in income distribution despite economic growth and poverty alleviation efforts (Statistics Indonesia, 2025). This gap between normative ideals and practical outcomes underscores the need for a deeper conceptual understanding of justice as articulated in Islamic economics. The findings of this review suggest that justice (‘adl) in Islamic economics is inherently multidimensional, encompassing moral, legal, and socio-economic dimensions aligned with the objectives of Shariah (maqasid al-Shariah). The study argues that revitalizing justice as the core paradigm of Islamic economics offers a coherent normative alternative to prevailing economic models, with significant implications for policy formulation and institutional design. The article concludes by proposing a conceptual framework that positions justice as the central axis of Islamic economic governance, while calling for future empirical research to translate normative principles into effective socio-economic policies.